Pengaruh Konflik Peran, Pengawasan Laporan Keuangan, dan Ambiguitas Peran Terhadap Komitmen Independensi Auditor Internal Pemerintah Daerah (Studi Empiris Pada Inspektorat Provinsi Sumatera Barat) - Riska Fitri Yeni; Nayang Helmayunita (Universitas Negeri Padang, 2016)
This study aims to determine the effect of conflict on the role, supervision of financial statements, role ambiguity to the commitment of local government internal auditor independence. This research is classified research causative. In this study, the population is the West Sumatra provincial inspectorate officials as many as 41 people. The sample in this study is total sampling. Data used in this study are primary and secondary data. Data collection method used is by using a questionnaire. The analysis used is multiple regression analysis using SPSS version 17. The results showed that: (1) conflict of roles significant effect on commitment to the independence, (2) the supervision of financial reports have a significant effect on the commitment to the independence, (3) ambiguity no significant effect on the commitment to the independenceKeywords: role conflict, supervision of financial reports, ambiquity, commitment to independence